Handbook of Nucleating Agents (2nd Edition) - Wypych, George (ChemTec Publishing, 2021)
Analyzes the existing literature and provides guidance on optimal selection of nucleating agents in order to increase production rates, improve the mechanical performance, and reduce the haze of polymeric products.